2010
DOI: 10.1161/circulationaha.109.901074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Aortic Root Dilation in Highly Trained Competitive Athletes

Abstract: Background-Few data are available that address the impact of athletic training on aortic root size. We investigated the distribution, determinants, and clinical significance of aortic root dimension in a large population of highly trained athletes. Methods and Results-Transverse aortic dimensions were assessed in 2317 athletes (56% male), free of cardiovascular disease, aged 24.8Ϯ6.1 (range, 9 to 59) years, engaged in 28 sports disciplines (28% participated in Olympic Games). In males, aortic root was 32.2Ϯ2.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 38 publications
5
97
0
2
Order By: Relevance
“…Fifteen of these 17 athletes demonstrated increases in aortic root dimensions over 8±5 years of follow-up, suggesting, as do our results, that aortic dilatation in athletes represents a pathological process and not a physiological adaptation to exercise. 40 The results of our meta-analysis cannot directly address the upper limits of normal root size in athletes, nor can they define the level of aortic dilation that would be considered pathological. We suggest that clinicians evaluating athletes make clinical decisions using the nomogram for aortic root size for the general population because the effect of elite training is small and clinically nonsignificant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Fifteen of these 17 athletes demonstrated increases in aortic root dimensions over 8±5 years of follow-up, suggesting, as do our results, that aortic dilatation in athletes represents a pathological process and not a physiological adaptation to exercise. 40 The results of our meta-analysis cannot directly address the upper limits of normal root size in athletes, nor can they define the level of aortic dilation that would be considered pathological. We suggest that clinicians evaluating athletes make clinical decisions using the nomogram for aortic root size for the general population because the effect of elite training is small and clinically nonsignificant.…”
Section: Discussionmentioning
confidence: 95%
“…Our results suggest that mild aortic enlargement is a normal adaptation to exercise training, but our results also indicate that large increases in aortic size are unusual Most studies included in our meta-analysis did not focus on aortic dimensions in athletes, and we had to extract aortic dimensions from their results. One study that evaluated mean aortic root dimensions and the prevalence of aortic root dilatation in 2317 Italian athletes 40 was not included in our meta-analysis. We did not include this large study because we sought to include only athletes defined as elite or at the national level by the authors, and this Italian study included AoD indicates aortic root diameter at aortic valve annulus; BSA, body surface area; CT, combined endurance-and strength-trained; ET, endurance-trained; F, female; M, male; MT, mixed-trained; n, number of participants; NR, not reported; and ST, strength-trained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular remodeling may also take in place in the descending abdominal aorta. 64 In contrast to the above work, Pelliccia et al 65 recently reported aortic root dimensions in a heterogeneous group of 2317 Italian athletes and found the largest measurements in endurance-trained athletes, specifically swimmers and cyclists.…”
Section: The Aortamentioning
confidence: 91%
“…On the contrary, Iskander et al [5] showed that male endurance athletes had greater AO diameters incomparison to strength athletes and controls, and strength athletes showed a non-significant trend towards greater dimensions at AO than controls. Pelliccia et al [6] assessed athletes of 28 different sports disciplines (n=1300) and showed that the aortic root dimension could be explained by weight, height, left ventricular mass and age, with the type of sports having a significant but lower impact. Their mean AO was greater (32.2 ± 2.7 mm) than in our soccer players (31.0 ± 2.85 mm) and 1.3% of the athletes had an enlarged AO (over 40 mm).…”
Section: Aortic Root Dimensioonmentioning
confidence: 99%